2014
DOI: 10.1007/s10587-014-0157-y
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of some classes of Banach spaces and non-universality

Abstract: Abstract. These notes are dedicated to the study of the complexity of several classes of separable Banach spaces. We compute the complexity of the Banach-Saks property, the alternating Banach-Saks property, the complete continuous property, and the LUST property. We also show that the weak Banach-Saks property, the Schur property, the Dunford-Pettis property, the analytic Radon-Nikodym property, the set of Banach spaces whose set of unconditionally converging operators is complemented in its bounded operators,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In particular, these classes are not Σ 1 2 . This result answers two questions posed by B. M. Braga in [6]. We recall that a Banach space X is said to have the Schur property if every weakly convergent sequence in X is norm convergent.…”
Section: 3(vi)])supporting
confidence: 64%
See 2 more Smart Citations
“…In particular, these classes are not Σ 1 2 . This result answers two questions posed by B. M. Braga in [6]. We recall that a Banach space X is said to have the Schur property if every weakly convergent sequence in X is norm convergent.…”
Section: 3(vi)])supporting
confidence: 64%
“…Therefore, it follows from the Tsirelson space method that the class of all separable Banach spaces with the Schur property is not coanalytic. Using a tree space method developed in [3], it can be shown that this class is not analytic (see [6,Theorem 27]). Our proof of the proper complexity result (Theorem 1.3) can be considered as a combination of these two methods.…”
Section: Lemma 38 There Exists a Borel Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…(V) If a separable Banach space X is isomorphically universal for separable Schur spaces, then it is actually isomorphically universal for all separable Banach spaces. This follows from methods in [3] (see [6,Corollary 51]). We are able to prove the isometric version of this statement (see Remark 3.7).…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…For each T ∈ Tr, let X 2,C[0,1],T be the metric space define above. An easy transfinite induction on the order of T gives us that, for all well-founded trees T ∈ Tr, the space X 2,C[0,1],T has the Banach-Saks property (see [Bra14], Theorem 14). Also, if T ∈ IF, it is clear that C[0, 1] linearly isometrically embeds into X 2,C[0,1],T .…”
Section: Complexity Of Some Asymptotic Notions and Applicationsmentioning
confidence: 99%